2018
DOI: 10.1029/2017rg000591
|View full text |Cite
|
Sign up to set email alerts
|

The Global Food‐Energy‐Water Nexus

Abstract: Water availability is a major factor constraining humanity's ability to meet the future food and energy needs of a growing and increasingly affluent human population. Water plays an important role in the production of energy, including renewable energy sources and the extraction of unconventional fossil fuels that are expected to become important players in future energy security. The emergent competition for water between the food and energy systems is increasingly recognized in the concept of the “food‐energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
300
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 559 publications
(303 citation statements)
references
References 518 publications
(884 reference statements)
1
300
0
2
Order By: Relevance
“…Terrestrial evapotranspiration (ET) is the sum of soil and open water evaporation, plant transpiration, and rainfall interception by the canopy. ET is a critical process linking water resources (Gedney et al, ; Oki & Kanae, ) and carbon–climate feedbacks (Field, Jackson, & Mooney, ; Ponce‐Campos et al, ; Shukla & Mintz, ; Zeng, Piao et al, ), and understanding the ET process has important implications for agricultural management (Allen, Pereira, Raes, & Smith, ; D'Odorico et al, ; Fisher et al, ). When surface water supply is unlimited, ET reaches an upper limit bounded by atmospheric evaporative demand, also known as potential evapotranspiration (PET).…”
Section: Introductionmentioning
confidence: 99%
“…Terrestrial evapotranspiration (ET) is the sum of soil and open water evaporation, plant transpiration, and rainfall interception by the canopy. ET is a critical process linking water resources (Gedney et al, ; Oki & Kanae, ) and carbon–climate feedbacks (Field, Jackson, & Mooney, ; Ponce‐Campos et al, ; Shukla & Mintz, ; Zeng, Piao et al, ), and understanding the ET process has important implications for agricultural management (Allen, Pereira, Raes, & Smith, ; D'Odorico et al, ; Fisher et al, ). When surface water supply is unlimited, ET reaches an upper limit bounded by atmospheric evaporative demand, also known as potential evapotranspiration (PET).…”
Section: Introductionmentioning
confidence: 99%
“…Some previous studies focused on the FEW flows and nexus in watersheds, cities, megacities and regions (Kennedy et al 2015, Endo et al 2017, Cai et al 2018, Gragg et al 2018, Taniguchi et al 2018, Yang and Wi 2018, which furthered our understanding of the internal characteristics of the system. Studies have also shown that changes in one system have profound effects on other systems, because of the interdependencies and interactions between food, energy and water subsystems (Hoff 2011, Al-Saidi and Elagib 2017, Scanlon et al 2017, Cai et al 2018, D'Odorico et al 2018. In addition, the external factors, such as rapid population growth, urbanization, economic development and climate change, will affect the production and supply of these resources and enhance the demands for food, energy and water (Hanjra and Qureshi 2010, Allan et al 2013, Seto and Ramankutty 2016, Qin et al 2019.…”
Section: Introductionmentioning
confidence: 99%
“…Growing human populations and economic development drive increases in global demand for food and energy, interlinked sectors that heavily rely on limited water resources (World Economic Forum, 2011). Dams produce hydropower, provide water for food production, modify water flows, and restructure fisheries, placing them at the center of the challenge to sustainably manage the food-energy-water (FEW) nexus (D'Odorico et al, 2018). With 3,700 large hydropower dams planned worldwide (Zarfl et al, 2015), understanding FEW tradeoffs is increasingly important.…”
Section: Introductionmentioning
confidence: 99%